Aux confins du politique et du juridique… ou du bon usage des déclarations de droits par les corps administratifs et judiciaires de la Révolution - Jérôme Ferrand (Clio@Themis)
Taking into account not only the problem of the legal value of declarations of rights, this research aims at apprehending the circumstances which led to their use under the Revolution. Those texts are indeed being exploited with a lot of circumspection by the administrative and judiciary bodies. Those who contemplate action while invoking them need to be able to evaluate the political outcome of their decisions. This is why the declarations of rights are essential for those who try to establish their authority in the arena of new constituted powers.